European Union: Ideology and symbolism - Kıraç, Ziya Kıvanç (My University, 2025)
Nation states constitute the attractive state systems of modern times. In the new order, the nation state, which is founded on a secular worldview, is built with symbols. Through symbolic contents such as flags, anthems and ceremonies, people build cultural unity. At the same time, they feel gratitude to the state to which they belong and bless being together. The feeling of being us is the most fundamental element that consolidates the nation. The European Union, which is expanding with the idea of Europeanness, is also trying to utilize various symbolic contents to build a super-identity. While the idea of a united Europe is not new, the concept of Europeanness is relatively new. Designing a new identity that transcends national identity nevertheless creates the necessity of finding common values to strengthen the sense of unity. The European Union is an important example of how the symbols of the nation-state work in a transnational system. In the context of recent studies of the union, which started out as an economic integration, the study is based on how symbols that are functional for nation states are positioned in a different system. Political determinations on European Union have been made in this context.
Keywords: European Union; Political Communication; Ideology; Symbolism; Nation State